STUDIES OF THE INFLUENCE OF INDEPENDENT VARIABLES (COVARIANTS) ON THE RELIABILITY CHARACTERISTICS OF EQUIPMENT - Fayzimatov Ulugbek Bahodirovich; Мирзаева Гулчера Сотиволдиевна; Abduvoxidov Shaxriyor Zikrullo oʻgʻli (Galaxy International Interdisciplinary Research Journal, 2022)
In this article, the study of the influence of independent variable covariants on the reliability characteristics of equipment.